2013
DOI: 10.9790/0837-1234756
|View full text |Cite
|
Sign up to set email alerts
|

Credit Management and Bad Debt In Nigeria Commercial Banks –Implication For development

Abstract: This paper examines the causes of bad and doubtful debt in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Nonperforming Loans are caused by debtors' failure to pay back their principal and interest when they fall due, which has a negative impact on the creditor's cash flow (Agu & Okoli, 2017). As soon as they are described as nonperforming debt, there is concern that the borrower will not be able to cover the whole amount owed, plus interest (Chelagat, 2020;Awunyo, 2017).…”
Section: Nonperforming Loansmentioning
confidence: 99%
“…Nonperforming Loans are caused by debtors' failure to pay back their principal and interest when they fall due, which has a negative impact on the creditor's cash flow (Agu & Okoli, 2017). As soon as they are described as nonperforming debt, there is concern that the borrower will not be able to cover the whole amount owed, plus interest (Chelagat, 2020;Awunyo, 2017).…”
Section: Nonperforming Loansmentioning
confidence: 99%
“…But experiences over the years have shown that inadequate credit analysis and sound judgment of loans application have resulted in unperforming loans. Provision of credits according to Agu and Basil (2013), which are in the form of loans and advances, are the total amount of money a given bank lends out to its customers at any given period of time. In providing credits for business ventures, banks should as a matter of importance take all necessary steps to ensure that advances are granted to those customers who can and will make judicious use of loans so that repayment will not become a problem.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the imports of such magnitude to other sectors of the economy is causing great concern to government and scholars (Akudugu, 2013). This predicament will continue to rear its ugly head especially when lowly financial reserve of the smallholding farmer, the farming population is put into considerations to engage into innovative farming activities (FAO, 2021) The aforesaid the farming group financial scenario could be related to among others, the poor rural financial market that exits in most countries in sub-Saharan Africa (Agu, and Okoli, 2013). In effect, most of the farmers satisfy their credit needs through engaging in institutional loan source.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural credit precisely is necessary in order to take advantage of new technologies in order to boost their production frontiers, enhances the welfare of the poor through consumption smoothening that decreases their vulnerability to short-term income and among others (Olomola;and Ade, 2002;Okonkwo -Emegha, 2018, Achoja andAnarah, 2018). However, empirical studies on the loan repayment performances of the farmers have been with great dismay (Agu and Okoli, 2013;Chaudhary, M. A., and Ishfaq, 2003;Ume, Ezeano and Obiekwe, 2018;Okonkwo-Emegha et al, 2018).…”
Section: Introductionmentioning
confidence: 99%